-
If (a2 – b2) sinθ + 2ab cosθ = a2 + b2 , then tanθ = ?
-
-
2ab a2 - b2
-
a2 - b2 2ab
-
ab a2 - b2
-
a2 - b2 ab
-
Correct Option: B
(a2 - b2) sinθ + 2ab cosθ = (a2 + b2)
On dividing by cosθ ,
(a2 - b2) tanθ + 2ab = (a2 + b2)secθ
On squaring both sides,
(a2 - b2)2 tan2θ + 4a2b2 + 4ab(a2 - b2) tanθ = (a2 + b2)2sec2θ
⇒ (a2 - b2)2 tan2θ + 4ab(a2 - b2) tanθ + 4a2b2 = (a2 + b2)2 ( 1 + tan2θ )
⇒ (a2 + b2)2 tan2θ - (a2 - b2)2 tan2θ 4ab(a2 - b2)2 tanθ + (a2 + b2) - 4a2b2 = 0
⇒ tan2θ{ (a2 + b2)2 - (a2 - b2)2 } - 4ab(a2 - b2) tanθ + (a2 - b2)2 = 0
⇒ 4a2b2 tan2θ - 4ab(a2 - b2) tanθ + (a2 - b2)2 = 0
⇒ { 2ab tanθ - (a2 - b2) }2 = 0
⇒ 2ab tanθ - (a2 - b2) = 0
⇒ tanθ = | ||
2ab |